PEMANFAATAN SERBUK KACA SEBAGAI BAHAN TAMBAH AGREGAT HALUS UNTUK MENINGKATKAN KUAT TEKAN BETON - Kosim Kosim; Arfan Hasan (PILAR, 2014)
Concrete is a building which is composed by an aggregate (sand rocks), cement and water (plus the other ingredients can be additive or admixture). Much research has been done on the concrete technology to meet the needs in infrastructure development started from the street, buildings, bridges, etc. The more concrete and more widespread use of the increasing scale of development also shows the more concrete needs in the foreseeable future, thus affecting the development of concrete technology which will demand new innovations regarding the concrete itself The times in the era of globalization, this resulted in a rapid increase of the number of goods waste residu which existence can be a problem for life, one of which is the presence of household glass waste. In this regard the efforts made are the utilization of powder glass as fine aggregate additive to enhance strong press concrete. Glass powder is used as a supplement for is smooth, with the addition of different variations, it is hoped to provide strong value press the concrete which is more varied and can be determined the  optimum levels of glass powder. As for the variation of the addition of powder glass used is 0 %, 25 %, 50 %, 75 %, and 100 %, with tests on a 3-day, 7-day, 14-day and 28 days. The result shows that glass powder can increase the strength of the concrete of compressive strength of concrete press 12 % normal, whereas for the optimum proportion is 25%.